Management of Guidance and Counselling Services in Addressing Students’ Interpersonal Conflict (A Multiple-Case Study at SMP Negeri 19 Bandung and SMP PGII 1 Bandung) - Mardiyati Mardiyati; Waska Warta (Journal of Science and Education (JSE), 2026)
Interpersonal conflict is an increasingly visible problem in Indonesian lower secondary schools, as indicated by the 2024 monitoring report showing a sharp rise in bullying cases and peer tensions, thereby demanding a more systemic school-based response [1]. Yet school Guidance and Counselling (GC) services are often reactive, fragmented, and insufficiently managed, so they do not prevent conflict nor build students’ social competence. This study aims to analyze holistically how Guidance and Counselling management—implemented through the POAC cycle (Planning, Organizing, Actuating, Controlling)—can address students’ interpersonal conflict in a more adaptive and responsive way. Employing a qualitative approach with a multiple case study design at SMP Negeri 19 Bandung and SMP PGII 1 Bandung, data were collected through triangulated in-depth interviews, observation, and document analysis and were analyzed using Miles, Huberman, and Saldaña’s interactive model. The findings show that both schools implemented GC management systematically: planning used a Developmental Task Instrument (DTI/ITP) to map needs; organizing was supported by clear structures and detailed case SOPs; actuating utilized a range of adaptive intervention strategies such as the Restitution Triangle, cognitive counselling, and responsive services; and controlling was guaranteed through strict case documentation, confidentiality, and periodic evaluation. The study concludes that adaptive, collaborative GC management with strong procedural adherence to POAC is effective in reducing conflict incidents, improving communication, and developing students’ social competence, and it offers a practical model of Integrated School Conflict Management.